Evaluation of soil suitability for Tomato and Pepper sufficiency production in Odeda Area of Ogun State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
The increasing food demands and world population pose pressure on the agricultural sector. This has led to cultivating the land without proper soil assessment; hence, this study aimed to evaluate the suitability of some lands in the Odeda area of Ogun State, Nigeria, for the cultivation of tomatoes and pepper. A 3 hectare of land was surveyed using the free survey method, and the soil morphological properties were examined. The morphological result was used to grid the soils into four mapping units. Representative profile pits (P1, P2, P3, P4) were dug, and soil samples were collected at the pedogenic horizons. The samples were air dried and processed using laboratory standard methods. The laboratory result obtained was matched with the soil characteristics for tomato and pepper. The suitability evaluation (current and potential) was calculated using both linear and square root approaches of the parametric model. The organic carbon was moderate (1.23-2.97 %) at the surface in all the profiles except in P3. The total nitrogen and available phosphorus were moderate (0.21% and 21.57 mg/kg), respectively, at the surface in P2. All the soils were moderately suitable and potentially highly suitable for pepper. However, P1, P2, and P3 were marginally not suitable for tomato production. Soil suitability evaluation is highly recommended to ascertain the kind of crop a land is suitable for.
Keywords: Linear method; Morphology; Parametric approach; Soil; Square root method